Scenario planning for libraries - O'Connor, Steve (Henry Stewart Talks, 2012)
Pressure for change in libraries globally, Analysis of the environment of the digital information world, Disruptive forces on technology, Digital information, Scenario planning, Application of scenario planning to libraries and publishing environments, Development of scenarios, Future options
Archived at 2023/06/22